RETRACTED ARTICLE: MicroRNA-338-3p suppresses ovarian cancer cells growth and metastasis: implication of Wnt/catenin beta and MEK/ERK signaling pathways - Ruitao Zhang; Huirong Shi; Fang Ren; Wei Feng; Yuan Cao; Gailing Li; Zheying Liu; Pengcheng Ji; Minghui Zhang (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Downregulation of microRNA-338-3p (miR-338-3p) was detected in many malignant tumors, which indicated miR-338-3p might serve as a role of antioncogene in those cancers. The present study aimed to explore the roles of miR-338-3p in the growth and metastasis of ovarian cancer cells and elaborate the underlying possible molecular mechanism. Methods Multiply biomedical databases query and KEGG pathway enrichment assay were used to infilter possible target genes and downstream pathways regulated by miR-338-3p. Overexpression miR-338-3p lentiviral vectors were transfected into ovarian cancer OVCAR-3 and OVCAR-8 cells, cell proliferation, migration and invasion were analyzed by MTT, colony formation, transwell, Matrigel assay and xenograft mouse model. One 3′-untranslated regions (UTRs) binding target gene of miR-338-3p, MACC1 (MET transcriptional regulator MACC1), and its regulated gene MET and downstream signaling pathway activities were examined by western blot. Results Biomedical databases query indicated that miR-338-3p could target MACC1 gene and regulate Met, downstream Wnt/Catenin beta and MEK/ERK pathways. Rescue of miR-338-3p could inhibit the proliferation, migration and invasion of ovarian cancer cells, and suppress the growth and metastasis of xenograft tumor. Restoration of miR-338-3p could attenuate MACC1 and Met overexpression induced growth, epithelial to mesenchymal transition (EMT) and activities of Wnt/Catenin beta and MEK/ERK signaling in vitro and in vivo. Conclusions The present data indicated that restoration of miR-338-3p could suppress the growth and metastasis of ovarian cancer cells, which might due to the inhibition of proliferation and EMT induced by MACC1, Met and its downstream Wnt/Catenin beta and MEK/ERK signaling pathways.